Is Social Capital Associated with Hypertension in Adults Visiting Integrated Health Posts for the Elderly? - Nathanael Aditya Santoso; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Social capital has been shown to play an important role in influencing an individual's health, including the incidence of hypertension in adulthood. Adults with hypertension who usually receive services at elderly posyandu with high strata are less likely to develop hypertension than posyandu with low strata. This study aims to determine the relationship between social capital and hypertension in adults in elderly posyandu.Subjects and Method: This study is an observational analytical study with a cross-sectional approach conducted in 25 Posyandu Elderly from May 2024 to July 2024 A total of 200 adult research subjects were selected using stratified random sampling and simple random sampling. The independent variable in this study is social capital and the dependent variable is hypertension. Data collection was carried out using a questionnaire. The analysis test in this study is a multilevel model double logistic regression analysis test conducted using the STATA 13 model.Results: Each increase in one unit of the social capital score will be followed by a decrease in systolic blood pressure of 0.94 mmHg (b= -0.94; 95% CI = -1.48 to -0.40; p= 0.001) and a decrease in systolic blood pressure of 0.32 mmHg (b= -0.32; 95% CI = -0.56 to -0.08; p= 0.008). Each one-year increase in age will be followed by an increase in systolic blood pressure of 0.43 mmHg (b = 0.43; 95% CI = 0.16 to 0.70; p = 0.002) and an increase in diastolic blood pressure of 0.14 mmHg (b = 0.02; 95% CI = 0.26 to 0.70; p = 0.018). There was no difference in systolic blood pressure between men and women (b= -2.84; 95% CI = -8.04 to 2.36; p= 0.284).Conclusion: Individuals who have good social capital lower the risk of hypertension. Increasing age and gender of women increases the risk of hypertension.